التعليم المبني على اللعبة اللغوية (تكنولوجيا التعليم المقترح لتعليم مهارة الكلام في المستوى الثانوي) - Abdul Haris (PPs UIN Maulana Malik Ibrahim Malang, 2010)
It is argued that language learning is hard and sometimes frustrating. Constant effort and pleasant condition are required in order to keep students motivated in learning language. One interesting strategy to make language teaching more effective and enjoyable is by using games. Games have some benefit for teachers and students. They help teachers not only to create contexts in which the language is useful and meaningful, but also to help and encourage students to sustain their interest and work. In addition, games provide intensive and meaningful practice of language.This article deals on a strategy of teaching Kalam (Arabic speaking) based on games for Madrasah Aliyah students. The strategy to practice it in teaching language will be the focus of the discussion.Keywords: Games, Kalam, Madrasah Aliyah